Rhenium polyhydride complexes of boron-hydride ligands and their application in catalysis - Donnelly, Liam J. (The University of Edinburgh, 2021)
The synthesis of transition metal complexes containing metal-boron bonds is of particular interest due to the relevance of these complexes as intermediates in catalytic C–X (X = H or halogen) borylation to prepare synthetically valuable organoboronate esters. The most widely used catalysts are Ir complexes typically of the form [Ir(Bpin)3(L)2], where L is a neutral monodentate or bidentate ligand, and invoke an Ir(III)/Ir(V) redox couple. In the past 30 years metal-oxos have been studied in the activation of X–H (X = B, Si, P) bonds for applications in catalytic hydrofunctionalisation reactions. The mechanism of these reactions can proceed by functionalisation and/or cleavage of the M=O bond to produce compounds that are inaccessible by conventional methods. However, this reactivity has not been significantly explored for anionic metal-oxo complexes (e.g. ReO4¯, RuO4¯ and WO4 2¯). This thesis presents the synthesis of a number of rhenium polyhydride complexes of boron-hydride ligands from perrhenate (ReO4−), the structural characterisation of these complexes, their application in C–H borylation catalysis and hydroboration, and the exploration of the mechanisms of these reactions. Chapter One introduces C–H functionalisation catalysis and the relevance of transition metal polyhydride and transition metal dihydroborate/σ-borane/boryl complexes as catalysts, and catalytically-relevant intermediates, in this chemistry. Previously reported methods for X–H (X = B or Si) activation by high oxidation transition metal-oxo complexes are also discussed. Chapter Two details the synthesis and characterisation of the reactive rhenium boron-polyhydride anion [K(DME)(18-c-6][ReH7(Bpin)3] by exhaustive deoxygenation of the commercially available ReO4−anion with pinacol borane (HBpin). This complex is shown to be a reagent for the stoichiometric C–H borylation of carboarenes with high meta regioselectivity. The reaction with other hydroboranes is also described, resulting in reductive Bpin substitution to form new anionic dihydroborate complexes. Chapter Three describes how [K(DME)(18-c-6][ReH7(Bpin)3], either isolated or prepared in situ, is a catalyst for the 1,4-hydroboration of N-heteroaromatic substrates under simple operating procedures. A full description of the optimisation of the reaction conditions and substrate scope is presented. A mechanistic investigation of the hydroboration reactivity is outlined and used to elucidate the catalytic cycle of this reaction. The use of other anionic metal-oxo complexes for hydrofunctionalisation catalysis is also discussed. Chapter Four details the synthesis and characterisation of phosphine-ligated Re boron-polyhydride complexes through the reductive substitution of HBpin from [K(DME)(18-c-6][ReH7(Bpin)3] with mono- and bidentate phosphine ligands. In particular, the synthesis of σ-borane complex [K(18-c-6)][ReH4(η2-HBpin)(dppp)] is highlighted which, upon protonation, forms the neutral boryl complex [ReH6(Bpin)(dppp)]. The catalytic activity of [ReH6(Bpin)(dppp)] in the C–H borylation of heteroaromatics is described, and a full substrate scope and mechanistic study is outlined. Chapter Five presents a summary of the work presented in this thesis, and Chapter Six outlines the experimental procedures and analytical data for all described compounds and complexes.
Keywords: catalysts development; organoboron compounds; rhenium complexes; boron reagents; C–B bonds